Design, Development and Calibration of a Drive Wheel Torque Transducer for an Agricultural Tractor - Abdelmotalab Fadlelmola, Kheiralla; Yahya, Azmi; Bardaie, Muhamad Zohadie; Wan Ismail, Wan Ishak (Universiti Putra Malaysia Press, 2003)
An appropriate transducer unit for measuring the drive wheel torque of a tractor was designed, developed and calibrated. The unit adopts a design having an extension shaft mounted in between the rear wheel axle flange and rear wheel rim of a tractor. Resistance type strain gauges were bonded on the shaft circumferential surfaces into a Wheatstone bridge circuitry for a standard torque measurement configuration. The bridge circuitry on each side of the rear drive axle was interfaced to a data acquisition system on board a tractor via a slip ring at the drive shaft end. Each transducer unit has been designed for a torque range of 0 to 32 kNm with a sensitivity of 14.492 J.lStrain/kNm. Static calibration tests on the transducer revealed excellent measurement linearity and measurement accuracy with coefficients of correlation or R2 equal to 0.9994 and 0.9994, respectively. The transducer hysteresis for static measurement was not significant. The transducer measurement errors were not more than 0.20% and 1% of the measured torque magnitudes under static and simulated dynamic measurements, respectively. Field demonstration test showed that the measurement for the torque magnitude at the rear wheel of the tractor was satisfactory. The data acquisition system had successfully scanned and recorded the signals from both transducers. These transducer units are part of the complete instrumentation system in the Massey Ferguson 3060 tractor to be used in the generation of comprehensive database on the power and energy requirements of the tractor-implement working in the field.